Transfers matter most: How changes in transfer systems of Canada and the United States explain the divergence in household poverty levels from 1974-1994 - Dan Zuberi (Luxembourg Income Study (LIS), 2001)
Three decades ago, Canada and the United States shared almost identical relative poverty and inequality levels. Yet despite experiencing similar macro-level social and economic transformations from 1974 to 1994 , the two nations have experienced diametrically opposite trends in relative household poverty. While levels of poverty increased in the U.S. during this period, Canada has experienced declining household poverty. Several institutional economists have utilized the comparative case of Canada to emphasize the important role of one kind of institution for explaining differences in poverty or inequality rates at one point in time i . These economists have presented compelling evidence that institutional differences, and not broader cultural or economic differences, explain the poverty and inequality differences between Canada and the U.S. in the late 1980s. These institutional differences include unionization policy and social welfare packages. Yet despite the importance of these institutional differences for explaining differences in poverty or inequality levels at one point in time, my analysis of Luxembourg Income Survey (LIS) data on Canada and the U.S. over this period clearly demonstrates that it is the different ways each nation has reformed their transfer systems over this period, and not other institutional differences or reforms, that comprehensively explain the divergent trends in relative household poverty rates from 1974 to 1994. My analysis utilizes harmonized LIS data to identify the relative explanatory strength of different facets of the transfer systems for explaining the divergence in poverty from 1974-1994. Surprisingly, the breakdown analysis reveals that the divergent trends can largely be explained by differences in the structure and reform of each nation's Social Retirement benefits, a factor not mentioned as an explanatory factor in the previous literature. Differences in other 'Social Insurance' transfers and 'Means-Tested' benefits together also helped explain the divergence in poverty trends, but with less power than expected. The increased effectiveness of the Canadian transfers for reducing its relative household poverty rate compared to the American system over this period has consequences for explaining divergence in inequality and possibly health outcomes and other measures of well-being between these two nations.
Keywords: 330; Armut; Haushaltseinkommen; Einkommensumverteilung; Sozialpolitik; Kanada; USA